Intelligence and espionage - Lomas, Daniel W. B., author.
1 online resource
Keywords: Intelligence and Espionage: Secrets and Spies provides a global introduction to the role of intelligence-a key, but sometimes controversial, aspect of ensuring national security. Separating fact from fiction, the book draws on past examples to explore the use and misuse of intelligence, examine why failures take place and address important ethical issues over its use. Divided into two parts, the book adopts a thematic approach to the topic, guiding the reader through the collection and analysis of information and its use by policymakers, before looking at intelligence sharing. Lomas and Murphy also explore the important associated activities of counterintelligence and the use of covert action, to influence foreign countries and individuals. Topics covered include human and signals intelligence, the Cuban Missile Crisis, intelligence and Stalin, Trump and the US intelligence community, and the Soviet Bloc. This analysis is supplemented by a comprehensive documents section, containing newly released documents, including material from Edward Snowden's leaks of classified material. Supported by images, a comprehensive chronology, glossary, and 'who's who' of key figures, Intelligence and Espionage is an invaluable resource for anyone interested in the role of intelligence in policymaking, international relations and diplomacy, warfighting and politics to the present day.